2005
DOI: 10.1093/treephys/25.12.1511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated concentrations of atmospheric CO2 and tropospheric O3 on leaf litter production and chemistry in trembling aspen and paper birch communities

Abstract: Human activities are increasing the concentrations of atmospheric carbon dioxide ([CO2]) and tropospheric ozone ([O3]), potentially leading to changes in the quantity and chemical quality of leaf litter inputs to forest soils. Because the quality and quantity of labile and recalcitrant carbon (C) compounds influence forest productivity through changes in soil organic matter content, characterizing changes in leaf litter in response to environmental change is critical to understanding the effects of global chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 59 publications
6
67
0
Order By: Relevance
“…This phytotoxic pollutant may cause oxidative stress in the plants (FERREIRA;DOMINGOS, 2012;APRO et al, 2012) and changes in the mineral elements flux (MAYER, 1983), which can be responsible for the foliage fall. Liu et al (2005), in a FACE study, found higher litter production in an elevated [CO 2 ] + elevated [O 3 ] treatments, showing that the negative effect of ozone was offset by the positive effect of CO 2 . The authors also found small changes in litter chemistry caused by elevated O 3 combined with carbon dioxide, which influenced litter production rates and had potential to significantly alter stand-level chemical inputs to soil.…”
Section: Figura 4 -Curvas De Decomposição De Serapilheira No Parque Ementioning
confidence: 99%
“…This phytotoxic pollutant may cause oxidative stress in the plants (FERREIRA;DOMINGOS, 2012;APRO et al, 2012) and changes in the mineral elements flux (MAYER, 1983), which can be responsible for the foliage fall. Liu et al (2005), in a FACE study, found higher litter production in an elevated [CO 2 ] + elevated [O 3 ] treatments, showing that the negative effect of ozone was offset by the positive effect of CO 2 . The authors also found small changes in litter chemistry caused by elevated O 3 combined with carbon dioxide, which influenced litter production rates and had potential to significantly alter stand-level chemical inputs to soil.…”
Section: Figura 4 -Curvas De Decomposição De Serapilheira No Parque Ementioning
confidence: 99%
“…The reason for choosing this setup is to allow flexible root and leaf C/N ratios in order to avoid immediate N deficiency stress when enhancing C acquisition rates. It has been shown that root C/N ratios (Pendall et al, 2004;Gai-ping et al, 2006) as well as leaf C/N ratios (Liu et al, 2005) can increase in Free Air CO 2 Experiments experiments (FACE), though the interdependence between changes in root and leaf C/N ratios still needs investigation.…”
Section: Allocation Of N To Plant Organsmentioning
confidence: 99%
“…Terrestrial ecosystems are undergoing simultaneous changes in climate and biogeochemical cycles, and those changes could affect plant net primary production (NPP) positively or negatively. Changes such as elevated CO 2 , nitrogen deposition (Xia and Wan, 2008) and temperature increases (Raich et al, 2006) were found to enhance plant productivity, whereas elevated O 3 (Liu et al, 2005), drought (Zhao and Running, 2010) and acid deposition (Irving and Miller, 1981) generally decreased productivity. These changes in primary production could alter both the quality and quantity of above-ground litter inputs to soil (Liu…”
Section: Introductionmentioning
confidence: 98%